2005
DOI: 10.1097/01.ccx.0000158092.64795.cf
|View full text |Cite
|
Sign up to set email alerts
|

The value of venous oximetry

Abstract: Early goal directed therapy should be implemented in the initial resuscitation of septic patients. Measurement of central venous oxygen saturation can easily be applied in intensive care unit patients and offers a useful indirect indicator for the adequacy of tissue oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 26 publications
1
59
0
3
Order By: Relevance
“…Instead of obtaining a surrogate for mixed venous saturation, these methods yield information about the venous blood in the particular region of the body that is illuminated by the PPG probe. The mixed venous saturation is known to provide valuable clinical information (for example in contributing to the early goal-directed therapy algorithm for treatment of sepsis [15]); thus, it may seem that regional venous saturation is less useful in a clinical setting. However, there are two factors that mitigate this criticism.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of obtaining a surrogate for mixed venous saturation, these methods yield information about the venous blood in the particular region of the body that is illuminated by the PPG probe. The mixed venous saturation is known to provide valuable clinical information (for example in contributing to the early goal-directed therapy algorithm for treatment of sepsis [15]); thus, it may seem that regional venous saturation is less useful in a clinical setting. However, there are two factors that mitigate this criticism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the most suitable sites with respect to complete mixing are the right ventricular outflow tract and pulmonary artery [1,2]. Mixed venous oxygen saturation has been shown to be a surrogate for the balance between systemic oxygen delivery and consumption during treatment of critically ill patients [3]. Maintenance and monitoring of tissue oxygenation is one of the most important goals in the care of critically ill or unstable patients.…”
mentioning
confidence: 99%
“…and frequently accompanied by increased VO 2 (agitation, fever, pain, etc.). The circulation can compensate to some extent, but after a critical threshold severe oxygen debt and shock may occur [8].…”
Section: Anaemia and Oxygen Debtmentioning
confidence: 99%